PELATIHAN PEMASARAN DIGITAL BERBASIS KONTEN DALAM RANGKA PENGEMBANGAN WISATA SPIRITUAL DI DESA WISATA GUNUNG SALAK, TABANAN BALI - Suryaningsih, Ida Ayu Anggreni; Irwanti, Ni Ketut Dewi; Dewi, Desak Made Purnama (Universitas Mataram, 2025)
Spiritual tourism is one of the main potentials of Gunung Salak Tourism Village, Tabanan, Bali, with its unique attraction being 11 sacred springs used for melukat (purification) rituals. This potential has not been fully developed due to limited digital promotion by the local community. Therefore, this community service program aims to improve the villagers’ skills in content-based digital marketing to strengthen the branding of the spiritual tourism village. The methods included problem identification, training design, implementation of training and content creation assistance, and evaluation. The program was carried out from July to September 2025, focusing on assisting the community in managing the official social media accounts pkmdesagunungsalak on Instagram, TikTok, and YouTube. The results show an improvement in community skills, especially among the village youth, in producing photo, video, and digital narrative content. The village’s social media accounts gained more followers and engagement, while the branding of spiritual tourism through the 11 sacred springs became more widely recognized. In addition, local UMKM products began to be promoted through social media, gaining broader market opportunities. In conclusion, content-based digital marketing training effectively supports the development of spiritual tourism in Gunung Salak Village and enhances community participation in digital-based tourism promotion.